1965
DOI: 10.1039/tf9656100274
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of carbons and graphites by atomic oxygen kinetic studies

Abstract: The oxidation of three amorphous carbons and an artificial graphite by atomic oxygen has been studied in the temperature range 14 to 350'C. The plasma of the radio-frequency discharge used to produce oxygen atoms was not in contact with the carbon sample. The rate of oxidation, at a fixed temperature, is dependent upon the duration of the experiment. This rate is also temperature dependent and activation energies of 9.9 to 10-8 kcal mole-1 are reported. The reaction is approximately first order with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“…oxygen atoms and hydrogen atoms. [33][34][35] Several mechanistic interpretations have been suggested. 19,20,22,33,34 Because of the higher energy of vacancies and defects relative to the bulk surface, when the surface of graphite is exposed to reacting gases at high temperature, gasification reactions are initiated at vacancies or reactive defects by removing the atoms surrounding these sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…oxygen atoms and hydrogen atoms. [33][34][35] Several mechanistic interpretations have been suggested. 19,20,22,33,34 Because of the higher energy of vacancies and defects relative to the bulk surface, when the surface of graphite is exposed to reacting gases at high temperature, gasification reactions are initiated at vacancies or reactive defects by removing the atoms surrounding these sites.…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35] Several mechanistic interpretations have been suggested. 19,20,22,33,34 Because of the higher energy of vacancies and defects relative to the bulk surface, when the surface of graphite is exposed to reacting gases at high temperature, gasification reactions are initiated at vacancies or reactive defects by removing the atoms surrounding these sites. 23 Various experiments have shown that atoms and radicals probably have a degree of mobility on the surface 22 and can recombine to give observed products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found necessary in an extensive formulation of hypothetical elementary steps to invoke the existence of stationary and mobile initial oxidation products (step 4) in order to explain the varying selectivity between CO and CO 2 . The experimental evidence showed different TDS peaks for carbon-oxygen compounds and not for di-oxygen [91,83,93,85] which led the authors to consider only the possibility that reaction products are mobile and not activated oxygen. The process of oxygen activation was assumed to only be possible at the reaction sites themselves ("C" in the reaction scheme).…”
Section: The Reaction Of Oxygen With Carbonmentioning
confidence: 99%
“…The process of oxygen activation was assumed to only be possible at the reaction sites themselves ("C" in the reaction scheme). If the activation of molecular oxygen occurs by non-chemical means (glow discharge [83,93] or radiolysis [82]) the sensitivity of the overall reaction kinetics to the presence of graphene layers for oxygen activation is lost and a fully structure-insensitive process occurs. In the other extreme of a di-oxygen reaction on a perfect graphene layer reaction of excessive activated oxygen will always occur at the unavoidable external prism surfaces and very efficiently at the few intralayer defects.…”
Section: The Reaction Of Oxygen With Carbonmentioning
confidence: 99%